2017
DOI: 10.1080/13697137.2017.1279140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porcine placental extract on the mild menopausal symptoms of climacteric women

Abstract: Oral PPE at 300 mg/day improved the mild menopausal symptoms of climacteric women. Since oral PPE did not improve serum E2 and FSH levels, PPE is thought not to ameliorate hormonal balance itself but to improve subjective feelings of climacteric women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…Placental extracts prepared from human or animal placenta have been used as ingredients in medicines, health foods, and cosmetics. Orally administered placental extracts have been reported to be effective for menopausal disorders [ 15 , 16 ] and their symptoms (e.g., knee pain, shoulder stiffness, and wrinkles below the eyes) [ 17 19 ]. Togashi et al reported that an orally administered human placental extract inhibits alcohol-induced hepatic disorder in a mouse model [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Placental extracts prepared from human or animal placenta have been used as ingredients in medicines, health foods, and cosmetics. Orally administered placental extracts have been reported to be effective for menopausal disorders [ 15 , 16 ] and their symptoms (e.g., knee pain, shoulder stiffness, and wrinkles below the eyes) [ 17 19 ]. Togashi et al reported that an orally administered human placental extract inhibits alcohol-induced hepatic disorder in a mouse model [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 330 were excluded; 59 included fewer than 20 women per study arm and 54 were not an RCT; 126 did not clearly state a sample size calculation; 52 did not measure vasomotor symptoms as the primary outcome; 39 were secondary analysis. Following these exclusions, 214 RCT were included…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action of placental extracts in the wound healing is associated with the increase of TGF- β in the early phase of regeneration and VEGF in the late phase, as well as with the presence of FGF, amplification of angiogenesis, and the increase of expression of CD31 [ 28 , 60 ]. Application of placental extracts in menopausal disorders allowed reducing the number and severity of hot flushes, irritability, and normalize hormonal profile [ 54 , 61 ]; the amount of estrogen receptors in the experiment was increased, and the effects of vaginal atrophy were reduced, while the activity of osteoblasts was improved [ 53 ]. Experimental studies on the effect of placental extracts on behavior and physical condition in the animal model showed decrease in symptoms of fatigue and increased resistance to physical stress [ 53 , 62 ].…”
Section: Placental Extractsmentioning
confidence: 99%